Improving Sonic Rarefactions in Elastic Vessels: Application to the Tourniquet Manoeuvre - Mairal, Juan; Murillo, Javier; García Navarro, Pilar (Jornada de Jóvenes Investigadores del I3A, 2022)
Elastic vessels like arteries and specially veins are prone to sharp changes in their area or external pressure. These phenomena create discontinuities due to a sudden jump on mechanical properties, which is a challenge when trying to simulate unsteady blood flow circulation. This work compares numerical methods to face this challenge in the context of a finite volume model.